Challenges And Benefits Of Implementing Green Building Technology In Building Construction Projects - Lim, Zen Yang (Universiti Sains Malaysia, 2019)
Green building technology (GBT) is the application of processes that are environmentally responsible and resource-efficient throughout a building's life-cycle. GBT has raised the public’s awareness in recent years due to global climate change. The construction industry is also aware that natural resources will be depleted if it does not practise sustainable development. Based on the fact that the design of built environment has various impacts on all of us, experts are beginning to focus on the design and construction of buildings using sustainable practices that will support the construction industry with a more responsible way to manage natural resources. Global construction output is predicted to grow significantly by year 2030. In order to preserve our environment for future generations, it is important to implement GBT in the building construction industry. Despite the enormous benefits of GBT, the implementation of GBT in Malaysia is still considered as slow due to various challenges. This study aims to determine the challenges and benefits of GBT implementation and to measure the weightage between the challenges and benefits of implementing GBT from sustainability perspectives. The result from questionnaire survey shows that the challenges of GBT implementation are more significant than the benefits of GBT implementation. The most significant challenge is “the role of government in promoting green building technology” with a Relative Importance Index (RII) of 4.54, out of 5.00. It is expected that this study can assist the construction industry’s stakeholders to understand GBT implementation for decision making and policy development, besides can be used as a reference for future comparative studies.